Social Media Affordances: Instagram Content as a Means to Perpetuate Gender Stereotification - Theodora Edra Pramaskara (Universitas Medan Area, 2022)
This article aims to find out more about the consequences of social media content on gender stereotyping of women. The existence of the internet, which cannot be separated from everyday life, allows humans to access information on digital media or social media more quickly and intensely, to fulfill various needs, such as the need for entertainment. Through the literature review data collection method and qualitative analysis on a number of Instagram accounts such as @Dagelan and @Alfysaga accounts, this study finds that social media has affordances to offer various types of contentÂ¾ including entertainment content, that users can enjoy as well. The focus of the problem in this research is uploads that sound gender stereotyping towards women, which in fact is still widespread in various types of entertainment content offered on social media platforms. By using the theory of media affordances and hegemony, in this study it is concluded that content creators can take advantage of Instagram's ability to reach many audiencesÂ¾which allows the consequences for gender-stereotyped entertainment content, for lasting and hegemonic because the audience continues to exist.